Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam - Mahmudah; Jumrodah; Atin Supriatin (PT. Sharia Journal and Education Center, 2024)
The principal plays a crucial role in improving the quality of Islamic Religious Education (PAI) learning, aiming to shape students' character in accordance with Islamic values. This article examines principals' strategies in enhancing the quality of PAI learning through a literature review method of 10 selected journals from 2020-2023. Data were obtained using the Harzing’s Publish or Perish application with the keyword